DECREASE OF REAL POWER LOSS BY ADAPTED ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2018)
In this paper, Adapted Flower Pollination (AFP) algorithm is proposed to solve the optimal reactive power problem. Flower pollination algorithm has been improved by comprising of the elements of chaos theory, Shuffled frog leaping search and Levy Flight. In the AFP algorithm, the initial population is generated using the circle map, frog leaping local search is performed by each solution and when rand>p, modified Levy flight with integration of inertia weight in global pollination is performed on that particular solution. Proposed AFP algorithm has been tested in standard IEEE 57 bus test system and simulation results show clearly the better performance of the proposed algorithm in reducing the real power loss.